Empirical theology in texts and tables : qualitative, quantitative and comparative perspectives - Astley, Jeff.; Francis, Leslie J.; Robbins, Mandy. (Empirical Studies in Theology, 2009)
Empirical theology offers fresh and stimulating insights into the concerns of both the Church and the Academy. It does this by accessing relevant empirical evidence using the tools of the social sciences, and placing this evidence in the context of theological critique and contemporary debate. In this pioneering collection of focused essays, leading experts of empirical theology illustrate key perspectives within this rapidly expanding discipline. The first section of the book explores theoretical issues underpinning the main methods of obtaining empirical data, and the use of these data within theology. The other two sections display the role both of qualitative studies, and of the analysis of quantitative data, in exploring a range of theological beliefs and religious, social and educational concerns.